If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + -2 + -7z + 6 + -1(5z + 8) = 0 Reorder the terms: 4z + -2 + -7z + 6 + -1(8 + 5z) = 0 4z + -2 + -7z + 6 + (8 * -1 + 5z * -1) = 0 4z + -2 + -7z + 6 + (-8 + -5z) = 0 Reorder the terms: -2 + 6 + -8 + 4z + -7z + -5z = 0 Combine like terms: -2 + 6 = 4 4 + -8 + 4z + -7z + -5z = 0 Combine like terms: 4 + -8 = -4 -4 + 4z + -7z + -5z = 0 Combine like terms: 4z + -7z = -3z -4 + -3z + -5z = 0 Combine like terms: -3z + -5z = -8z -4 + -8z = 0 Solving -4 + -8z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -8z = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -8z = 0 + 4 -8z = 0 + 4 Combine like terms: 0 + 4 = 4 -8z = 4 Divide each side by '-8'. z = -0.5 Simplifying z = -0.5
| 112-u=183 | | 5(7x-7)=15x | | 60+15x=210 | | (-28)+139= | | 17+[3+(-9)]= | | =5(x-4)-10 | | [-15+(-4)]+7= | | 7(8x-3)=28x | | Sqrt(x)=6 | | 6=2x+4yx+2y | | 6-a=0.33333333333333333333333333333333(9a-8) | | 12x+9-4x-4=3x-7-x-x+30 | | (8x+5)-(9x-9)= | | -35-6a=-9(5a+3) | | 2(x-3)=0.5(x-6) | | D=4t | | 9(7c+3)=-34 | | (-28)+138= | | (3x+1)(-x+2)+2(3x+1)(2x-1)=0 | | [-5+(-1)]+[5+(-4)]= | | 14+(-9)+(-12)= | | -3a^3b(9a^5+5ab-b^3)= | | 7(3a-x)=3b | | 51+(-104)+(-78)= | | 3x-7/4=2 | | 9x-5.5=7x+3.5 | | 12+[4+(-9)]= | | 15x+8y=130 | | [-16+(-6)]+4= | | 25x-4(4x+6)=-70 | | v=(x+3)(2x-5)(x-4) | | 4x+13=12x-3 |